Evolutionary loss of 8-oxo-G repair components among eukaryotes - Jansson, Kristina (BioMed Central, 2010)
BACKGROUND: We have examined the phylogenetic pattern among eukaryotes of homologues of the E. coli 7,8-dihydro-8-oxoguanine (8-oxo-G) repair enzymes MutY, MutM, and MutT. RESULTS: These DNA repair enzymes are present in all large phylogenetic groups, with MutM homologues being the most universally conserved. All chordates and echinoderms were found to possess all three 8-oxo-G repair components. Likewise, the red and green algae examined have all three repair enzymes, while all land-living plants have MutY and MutM homologues, but lack MutT. However, for some phyla, e.g. protostomes, a more patchy distribution was found. Nematodes provide a striking example, where Caenorhabditis is the only identified example of an organism group having none of the three repair enzymes, while the genome of another nematode, Trichinella spiralis, instead encodes all three. The most complex distribution exists in fungi, where many different patterns of retention or loss of the three repair components are found. In addition, we found sequence insertions near or within the catalytic sites of MutY, MutM, and MutT to be present in some subgroups of Ascomycetes. CONCLUSION: The 8-oxo-G repair enzymes are ancient in origin, and loss of individual 8-oxo-G repair components at several distinct points in evolution appears to be the most likely explanation for the phylogenetic pattern among eukaryotes.